A semi-automatic 3D ultrasound reconstruction method to assess the true severity of adolescent idiopathic scoliosis. - Vo, Quang N.; Le, Lawrence H.; Lou, Edmond (Medical & Biological Engineering & Computing, 2019)
Adolescent idiopathic scoliosis (AIS) is a three-dimensional (3D) spinal deformity. Current practice uses the Cobb method to measure spinal severity on postero-anterior (PA) radiographs. This method may underestimate spinal deformity and exposes patients to ionizing radiation, increasing the risk of cancer. This paper reports a new 3D ultrasound method using the voxel-based reconstruction technique with bilinear interpolation to reconstruct a 3D spinal image and measure true spinal curvature on the plane of maximal curvature (PMC). Axial vertebral rotation (AVR) was measured on the 3D image and utilized to estimate the PMC. In vitro phantom experiments and in vivo clinical study were conducted to evaluate reconstruction accuracy and measurement reliability. The in vitro study showed a high accuracy of the reconstruction of vertebrae with the mean absolute difference (MAD) < 3 mm. The in vitro and in vivo measurements of AVR were reliable (> 0.90). The in vivo study also showed high intra- and inter-rater reliabilities of the PA and PMC Cobb angle measurements with ICC values > 0.90 and MADs within the clinical accepted tolerances. The PMC Cobb angles were up to 7° greater than their corresponding PA Cobb angles. This method demonstrated a non-ionizing radiation method to assess the actual severity of AIS. Graphical abstract Adolescent idiopathic scoliosis (AIS) is a lateral curvature of spine with vertebral rotation. Using the Cobb method to measure spinal severity on postero-anterior (PA) radiographs may under estimate its severity.